If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -1)(x + 9) = 0 Reorder the terms: (-1 + X)(x + 9) = 0 Reorder the terms: (-1 + X)(9 + x) = 0 Multiply (-1 + X) * (9 + x) (-1(9 + x) + X(9 + x)) = 0 ((9 * -1 + x * -1) + X(9 + x)) = 0 ((-9 + -1x) + X(9 + x)) = 0 (-9 + -1x + (9 * X + x * X)) = 0 (-9 + -1x + (9X + xX)) = 0 Reorder the terms: (-9 + 9X + -1x + xX) = 0 (-9 + 9X + -1x + xX) = 0 Solving -9 + 9X + -1x + xX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9X + -1x + 9 + xX = 0 + 9 Reorder the terms: -9 + 9 + 9X + -1x + xX = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 9X + -1x + xX = 0 + 9 9X + -1x + xX = 0 + 9 Combine like terms: 0 + 9 = 9 9X + -1x + xX = 9 Add 'x' to each side of the equation. 9X + -1x + x + xX = 9 + x Combine like terms: -1x + x = 0 9X + 0 + xX = 9 + x 9X + xX = 9 + x Reorder the terms: -9 + 9X + -1x + xX = 9 + x + -9 + -1x Reorder the terms: -9 + 9X + -1x + xX = 9 + -9 + x + -1x Combine like terms: 9 + -9 = 0 -9 + 9X + -1x + xX = 0 + x + -1x -9 + 9X + -1x + xX = x + -1x Combine like terms: x + -1x = 0 -9 + 9X + -1x + xX = 0 The solution to this equation could not be determined.
| 11.2t+2=4.7t+44.90 | | 9-4d=3 | | 2x+5y=-44 | | 2.1x+97=4.7x+6 | | x^2-4xy^2=0 | | 5(2x-1)+3(4-9x)=0 | | 12x-5=7x+60 | | 1x-8=-6x+6 | | 2x+3=4+6x | | 7(x-3)=84 | | 11f+6=12f+6 | | -2z+7=21 | | 8(3s+6)= | | uk+un=r | | 4(4-c)=3(5-c)+4 | | 10c+8=14c-20 | | 17=-b+6 | | 8(2l+1)= | | 6a-10=4a+2 | | 2(2w-6)+2(w)=3(w+8) | | 4(a-3)= | | 9+3x=8x+12 | | X(90)=1050+375 | | (u+4)*10= | | 95.30=19.95+0.55x | | -5x-2(4-2x)=2+7 | | 15+.20m=25.00+.10m | | x+8+16=0 | | (q-5)*2= | | -5-2(4-2x)=2+7 | | 2x+44=x-12 | | 2(w-6)+2(w)=3(w+8) |